Commoners and the assize of novel disseisin, 1194-1221 - Musson, Janice (2016)
Commoners' use of the assize of novel disseisin, or recent dispossession, and the action itself are fundamental to the creation and evolution of English common law. The assize was issued by Henry II in 1166 for the resolution of property disputes and could be brought only before the royal courts, which had the effect of removing many such disputes from seigneurial jurisdiction. It was immediately popular and continued in everyday use for almost 300 years. The thesis considers commoners' approach to the action from the earliest accounts of their cases recorded in the Plea Rolls, which are extant from 1194, focusing upon unfree litigants despite their official exclusion from the assize, the poor, and women. It finds that they were attracted by, inter alia, the action's accessibility to all free men and women, however impoverished, its speed and reliability, and its use of writing to record the outcome of disputes. It was a time when the procedures of the nascent common law, the new opportunities it offered the populace, and literacy, were all in a state of flux. The cases show how and in what manner many humble people used the action to their advantage and also the reasons why others failed, indicating their view and understanding of their society.